Evolved Transcriptional Responses and Their Trade-Offs after Long-Term Adaptation of Bemisia tabaci to a Marginally Suitable Host. (26th July 2022) - Tadmor, Ella; Juravel, Ksenia; Morin, Shai; Santos-Garcia, Diego
Abstract: Although generalist insect herbivores can migrate and rapidly adapt to a broad range of host plants, they can face significant difficulties when accidentally migrating to novel and marginally suitable hosts. What happens, both in performance and gene expression regulation, if these marginally suitable hosts must be used for multiple generations before migration to a suitable host can take place, largely remains unknown. In this study, we established multigenerational colonies of the whitefly Bemisia tabaci, a generalist phloem-feeding species, adapted to a marginally suitable host (habanero pepper) or an optimal host (cotton). We used reciprocal host tests to estimate the differences in performance of the populations on both hosts under optimal (30°C) and mild-stressful (24°C) temperature conditions, and documented the associated transcriptomic changes. The habanero pepper-adapted population greatly improved its performance on habanero pepper but did not reach its performance level on cotton, the original host. It also showed reduced performance on cotton, relative to the nonadapted population, and an antagonistic effect of the lower-temperature stressor. The transcriptomic data revealed that most of the expression changes, associated with long-term adaptation to habanero pepper, can be categorized as "evolved" with no initial plastic response. Three molecular functions dominated: enhanced formation of cuticle structural constituents, enhanced activity of oxidation–reduction processes involved in neutralization of phytotoxins and reduced production of proteins from the cathepsin B family. Taken together, these findings indicate that generalist insects can adapt to novel host plants by modifying the expression of a relatively small set of specific molecular functions.